Factors affecting learning disabilities in mathematics: a study of central region of Nepal - Pandit, Dr. Ramjee Prasad (Tribhuvan University Journal, 2006)
The students whose achievement lagged behind their intellectual potential presents a serious problem to the parents, society and finally to the nation; instead of being the contributing members they turn out to be social problem and get involved in the most common social malaise-student on rest. Describing groups who have average or above average intelligence continuously failing to maintain normal progress in school subjects as learning disabled students, the teacher education programs in western countries like U.S.A. and Europe started the identification, diagnosis and serve them since 1963. But in developing countries, for example, in Nepal and India, although the efforts are directed towards this direction, no the considerable progress has yet been observed. So the present investigation was concerned with the identification of the causes of primary school children learning disabilities in mathematics (CLDM). 58 LD boys and 46 LD girls from 29 rural and 15 urban schools situated in different parts of central region of Nepal participated in this study. The analysis of these 104 LD students' bio-data revealed that the factors related to the children with learning disabilities in mathematics were the poor instruction, parents' adverse behavior to them, teacher's negligence in the class. It was suggested that the quality of teaching strategies and quality of instruction in the schools must be improved. Further research is needed for the generalization of the findings throughout the nation. Tribhuvan University Journal 2004/1 pp. 13-19